2018
DOI: 10.1002/chem.201803798
|View full text |Cite
|
Sign up to set email alerts
|

Redox Potential‐Dependent Formation of an Unusual His–Trp Bond in Bilirubin Oxidase

Abstract: Bilirubin oxidase (BOD) belongs to the family of blue multicopper oxidases, and catalyzes the concomitant oxidation of bilirubin to biliverdin and the reduction of molecular oxygen to water via a four-electron reduction system. The active sites of BOD comprise four copper atoms; type I copper (T1Cu) forms a mononuclear site, and a cluster of three copper atoms forms a trinuclear center. In the present study, we determined the high-resolution crystal structures of BOD from the fungus Myrothecium verrucaria. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 44 publications
0
23
0
1
Order By: Relevance
“… a) Scheme of the proposed multilayer gas diffusion electrode modified with the DdHydAB (1HFE) hydrogenase wired through the viologen‐modified polymers P(GMA‐BA‐PEGMA)‐vio and P(N 3 MA‐BA‐GMA)‐vio. b) Schematic of the dual gas diffusion membrane‐free H 2 /O 2 powered biofuel cell equipped with the bioanode depicted in (a) and an O 2 ‐reducing bilirubin oxidase (6IQZ) based biocathode operated in a direct electron transfer regime. Not drawn to scale.…”
Section: Figurementioning
confidence: 79%
“… a) Scheme of the proposed multilayer gas diffusion electrode modified with the DdHydAB (1HFE) hydrogenase wired through the viologen‐modified polymers P(GMA‐BA‐PEGMA)‐vio and P(N 3 MA‐BA‐GMA)‐vio. b) Schematic of the dual gas diffusion membrane‐free H 2 /O 2 powered biofuel cell equipped with the bioanode depicted in (a) and an O 2 ‐reducing bilirubin oxidase (6IQZ) based biocathode operated in a direct electron transfer regime. Not drawn to scale.…”
Section: Figurementioning
confidence: 79%
“…144,145 Akter et al identified a covalent bond between a surface tryptophan and one of the histidine residues coordinating the T1 Cu, and proposed that it raises the redox potential of the T1 site to match that of the bilirubin substrate. 146 In a "yellow" laccase from Sclerotinia sclerotiorum, Mot et al identified a surface tyrosine residue at the T1 site, which forms a reversible adduct with the electron-donor substrate. 124 The surface residues near the T1 site also influence the dipole moment of MCOs.…”
Section: Catalysis Science and Technology Mini Reviewmentioning
confidence: 99%
“… a) Schema der vorgeschlagenen Mehrschicht‐Gasdiffusionselektrode, modifiziert mit der DdHydAB (1HFE [28] )‐Hydrogenase, die durch die Viologen‐modifizierten Polymere P(GMA‐BA‐PEGMA)‐vio und P(N 3 MA‐BA‐GMA)‐vio kontaktiert wird. b) Schema der auf zwei Gasdiffusionselektroden basierenden membranfreien H 2 /O 2 ‐Biobrennstoffzelle, ausgestattet mit der in (a) dargestellten Bioanode und einer auf der O 2 reduzierenden Bilirubinoxidase (6IQZ) basierenden Biokathode, die in einem direkten Elektronentransfer‐Regime betrieben wird. Nicht maßstabsgetreu gezeichnet.…”
Section: Figureunclassified